Strong NFκB Expression is Associated With High-grade Dysplasia in Barrett's Esophagus. Issue 5 (May 2017) - El Jamal, Siraj M.; Yaseen, Alae A.; Alatassi, Houda; Slone, Stephen; Bishop, Barbara J.; Fraig, Mostafa
Abstract : Nuclear factor kappa B (NFκB) is a transcription factor that regulates the activation of genes involved in proinflammatory response and growth. In this study, we utilized immunohistochemical stains for 2 of the NFκB molecules (RELA and NFκB-1) to evaluate the expression of NFκB in Barrett's esophagus (BE). Forty-three cases of BE [17 cases with no dysplasia, 16 cases with low-grade dysplasia (LGD), and 10 cases with high-grade dysplasia (HGD)], 10 normal esophageal biopsies, and 9 cases of esophageal adenocarcinoma were evaluated. Expression of NFκB-1 and RELA did not occur in normal esophageal squamous mucosa. BE without dysplasia showed weak expression of RELA and NFκB-1 in 35% and 65% of cases, respectively. BE with LGD showed weak expression of RELA and NFκB-1 in 50% and 75% of cases, respectively. Strong expression of RELA and NFκB-1 did not occur in BE without dysplasia or with LGD. BE with HGD showed strong expression of RELA and NFκB-1 in 80% and 90% of cases, respectively. All cases of adenocarcinoma showed strong expression of both RELA and NFκB-1. There was a progressive increase in staining intensity of RELA and NFκB-1 along the metaplasia-dysplasia-adenocarcinoma pathway. Strong expression of NFκB is associated with HGD and adenocarcinoma ( P< 0.0001). We showed that strong expression of NFκB-1 and RELA correlates highly with BE with HGD and adenocarcinoma.